The Impact of Transfer Pricing, Thin Capitalization, and Firm Size on Tax Avoidance with Multinational Enterprise as a Moderating Variable - Indrastuti, Tri Dyah; Apriliawati, Yeti (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The government aims for Indonesia to become a developed country by 2045 to expect optimal tax revenues. There is a conflict of interest between the government that wants to maximize taxes and taxpayers who want to minimize taxes through tax avoidance practices. This study investigates the influence of transfer pricing, thin capitalization, and firm size on tax avoidance, with multinational enterprises as a moderating variable. The population comprises manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2021. The sample for this study was determined using purposive sampling, resulting in 13 selected companies. The analysis in this research employs panel data regression using Eviews 12. The results indicate that when analyzed individually, transfer pricing does not significantly impact on tax avoidance. However, both thin capitalization and firm size demonstrate a significant negative influence on tax avoidance. Furthermore, thin capitalization and firm size exert a significant positive influence on tax avoidance, a relationship that is moderated by multinational enterprises. Conversely, transfer pricing exhibits the opposite effect. Simultaneous tests reveal that transfer pricing, thin capitalization, and firm size collectively exert an effect on tax avoidance, which is further moderated by multinational enterprises.